2002
DOI: 10.1079/bjn2002521
|View full text |Cite
|
Sign up to set email alerts
|

Dietary myristic acid modifies the HDL-cholesterol concentration and liver scavenger receptor BI expression in the hamster

Abstract: The influence of myristic acid in a narrow physiological range (0·5 to 2·4 % of total dietary energy) on the plasma and hepatic cholesterol metabolism was investigated in the hamster. The hamsters were fed on a diet containing 12·5 g fat/100 g and 0·05 g cholesterol/100 g with 0·5 % myristic acid (LA diet) for 3 weeks (pre-period). During the following 3 weeks (test period), they were divided into four dietary groups with 0·5 % (LA), 1·2 % (LM), 1·8 % (ML) or 2·4 % (M) myristic acid. Finally, half the hamsters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(23 citation statements)
references
References 59 publications
1
19
0
3
Order By: Relevance
“…Methylparaben showed antioxidative activity and prevented lipid peroxidation in 6-hydroxydopamine-induced animals [54]. The predominant food component tetradecanoic acid (myristic acid) showed free radical scavenging activity [55] and cholesterol modulating activity in vivo [56]. Vaccenic acid demonstrated convincing hypolipidemic activity by decreasing hepatic lipogenesis in experimental rats [57].…”
Section: Discussionmentioning
confidence: 98%
“…Methylparaben showed antioxidative activity and prevented lipid peroxidation in 6-hydroxydopamine-induced animals [54]. The predominant food component tetradecanoic acid (myristic acid) showed free radical scavenging activity [55] and cholesterol modulating activity in vivo [56]. Vaccenic acid demonstrated convincing hypolipidemic activity by decreasing hepatic lipogenesis in experimental rats [57].…”
Section: Discussionmentioning
confidence: 98%
“…Original data from Pownall et al [8] have determined how molecular structure of PC independently regulate cholesteryl ester formation via LCAT action. Concerning dietary myristic acid (MA, 14:0), Loison et al [10] have recently reported in hamsters a positive correlation between plasma HDL concentration and the amount of MA in the diet.…”
Section: Introductionmentioning
confidence: 98%
“…Myristic acid has long been considered as having played a major role in the increase in blood cholesterol level in animals and humans, when provided at high level, exceeding 4% of dietary energy [9,10]. However, when its dietary level is moderate (1.0-2.5% of dietary energy) no evidence of deleterious effects of this specific fatty acid has been reported [11][12][13][14]25]. In humans, a moderate supply of myristic acid (1.8% of daily energy) was shown to improve lecithin cholesterol acyltransferase (LCAT) activity, which is considered beneficial in terms of HDL cholesterol concentration and reverse cholesterol transport [36].…”
Section: Discussionmentioning
confidence: 97%
“…For instance, short and medium chain SFA have been shown to have no increasing effect on plasma cholesterol in humans [8]. Myristic acid has deleterious effects on blood cholesterol level in animals and humans when provided at high level exceeding 4% of dietary energy [9,10], but these negative effects disappear when its dietary level is moderate (1.0-2.5% of dietary energy) [11][12][13][14]. Stearic acid has also been demonstrated to be neutral on plasma cholesterol concentrations [15] and to have no negative effect on thrombotic markers in humans [16].…”
Section: Introductionmentioning
confidence: 98%